Pengaruh Lingkungan Makro terhadap Transformasi Industri Perbankan di Indonesia : Tinjauan Konseptual PESTEL - Hari Satriyono (ITB AAS Indonesia Surakarta, 2026)
The banking industry in Indonesia is undergoing significant transformation driven by increasingly complex macro-environmental changes, including rapid digitalization, growing sustainability concerns, evolving customer behavior, and strengthened financial sector regulations. Understanding these macro-environmental dynamics is essential to explain the strategic transformation of the banking industry. This study aims to analyze how macro-environmental factors influence the transformation of the Indonesian banking sector using the PESTEL framework (Political, Economic, Social, Technological, Environmental, and Legal). This research adopts a conceptual review approach using secondary data derived from the sustainability reports of four major Indonesian banks : PT Bank Rakyat Indonesia Tbk (BBRI), PT Bank Central Asia Tbk (BBCA), PT Bank Negara Indonesia Tbk (BBNI), and PT Bank Mandiri Tbk (BMRI)—which represent the structure and strategic direction of the national banking industry. Data were analyzed using document analysis to identify patterns of strategic responses adopted by banks in addressing macro-environmental pressures. The findings indicate that the transformation of the Indonesian banking industry is mainly influenced by four dominant dimensions: technological, environmental, social, and legal factors. Technological developments accelerate digital banking transformation, environmental factors drive sustainable finance and ESG integration, social dynamics strengthen financial inclusion initiatives, and regulatory frameworks reinforce governance and transparency. The study proposes a conceptual model showing that banking transformation in Indonesia results from interactions between macro-environmental pressures and adaptive strategies adopted by banks to strengthen digital capabilities and sustainable finance practices.